Mapping of the associations that act as governance instruments for the RPPN in the Brazilian states - Ferrari, Gabriel Mathias; Mello, Nilvania Aparecida de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This article is about the mapping of Private Natural Heritage Reserves (RPPN) associations, which is a private conservation unit that is intended for environmental protection. The RPPN associations are organizations that bring together members/owners of these units in search of environmental protection cause strengthening by private properties. Through analysis of documents and interviews with people who are directly linked to the beforementioned associations, this study focused on observing the change in the quantity of associations in Brazil in the last two decades, and identifying the main challenges that are faced by those institutions. Scarce bibliography about RPPN associations makes this study original when raising these issues. The result shows that the quantity of associations has varied from seventeen to five in Brazil currently. Among the reasons pointed out that make management and maintenance difficult, the financial factor is found, it means the shortage of resources for daily activities. Paradoxically, the environmental protection cause through these associations of private properties may have political strength that can lead to a change in the current scenario. Understanding the constraints faced by those institutions enhance the environmental protection cause by private properties, what directly contributes to the environmental conservation.
Keywords: RPPN; Proteção ambiental por propriedades privadas; RPPN Associations